Proposals for the Second Five Year Plan Scheduled Tribes Vol. No. II Government of Madhya Bharat - Planning Commission (Planning Commission, 1955)
The sphere of Welfare activities has been rapidly widening for the last two years. It would be much more expanded during the period of the Second Plan. The success of Plan much depends upon the adequacy of machinery set-up to organise and execute the schemes. The experience of past years has illustrated that desired objectives and targets would not be achieved unless increase in the administrative staff takes place in proportion to the work. This aspect of the problem has been kept in view while framing proposals of the schemes to be included in the Second Five Year plan.
Government of Madhya Bharat, Department of Harijan and Tribal Welfare